Kajian Kearifan Lokal Euphorbiaceae Sebagai Tumbuhan Obat oleh Masyarakat Aceh - Zumaidar Zumaidar (Jurnal Agrista, 2009)
Indigenous Knowledge Study of Euphorbiaceae as a Medicinal Plant by Acehness PeopleABSTRACT. A research about study of indigenous knowledge of euphorbiaceae as medicinal plant by Acehness people was done on June until October 2007. The research was carried on 9 district of Banda Aceh city which aimed to get the knowledge from acehness people about medicinal effect of euphorbiaceae plant such as: Euphorbia pulcherrima, Euphorbia hirta, Phyllanthus urinaria, Ricinus communis, Aleurites molucccana, Manihot esculenta, Jatrophe curcas, Codiaeum variegatum, dan Hevea brasilensis. The method used was PRA (Participatory Rural Appraisal) which purposive sampling for respondences: keuchik, tuha peut, dan tabib on every villages. The parameters of this research was: the kinds of disease, organ of plant used, mixing way of medicine, and how to use. The result showed that from 455 respondents, all of them, have the indigenous knowledge about Jatropha curcas as medicinal plant. Contrary of Euphorbia pulcherrima, Manihot esculenta, Codiaeum variegatum, and Hevea brasilensis are unknown as medicinal plant. Phyllanthus urinaria is the most species used, because can heal 10 disease.